Testing gravitational physics on large and small scales - Traykova, D (2021)
Einstein's theory of General Relativity has long been considered the standard theory of gravity, as it provides us with an extremely good description of how objects interact gravitationally at all scales. The Standard Model of cosmology, based on General Relativity, provides an excellent description of how astrophysical objects and matter interact. However, it requires the addition of two exotic ingredients: cold dark matter and dark energy, in order to correctly account for some observational phenomena, such as the accelerated expansion of the universe and the flat galaxy rotation curves that we observe. This has prompted the exploration of alternative theories of gravity, which can account for these observations without invoking the need for one or both of these exotic types of matter.